A Rapidly Convecting Lava Lake at Masaya Volcano, Nicaragua - Pering, Tom D.; Ilanko, Tehnuka; Wilkes, Thomas C.; England, Rebecca A.; Silcock, Siân R.; Stanger, Leigh R.; Willmott, Jon R.; Bryant, Robert G.; McGonigle, Andrew J. S. (Frontiers in Earth Science, 2019)
Lava lakes provide a rare opportunity to study conduit flow processes through direct observation of the exposed magma surface. The recent lava lake activity at Masaya volcano (Nicaragua), which commenced in 2015, displayed several unusual phenomena. We report on the dynamics of this rapidly convecting lake, which, to the best of our knowledge manifested the highest lava flow velocities ever reported for a lava lake: 13.7–16.4 m s−1, in addition to unusual fluid dynamic behavior involving alteration in surface flow direction. We studied this system with multiparametric and high time resolution remote sensing measurements, performed during June 2017, including ultraviolet camera observations of SO2 emission rates, near infrared thermal camera measurements and video analyses of the lake surface. Median SO2 emission rates of 3.1 (±0.8) and 3.7 (±0.9) kg s−1 were found, which are lower than previously published estimates, and could represent challenging remote sensing conditions or a waning in lava lake activity. Video analyses enabled characterization of frequent bursts of approximately hemispherical spherical-cap bubbles on the surface with diameters ranging 0.6–8.5 m (median of 2.6 m), and calculation of individual bubble masses, which contribute to active bubble bursting values estimated at 1.9 to 3.9 kg s−1. We show that only a small fraction, 7–17%, of total emission volumes are contributed by these bubbles, based on estimated emission rates of 22.5 and 26.9 kg s−1. Furthermore, periodicity analysis reveals regular 200–300 s oscillations in SO2 emissions. These are not shared by any of our other datasets and particularly during the contemporaenously acquried thermal data, hence, we tentatively assign an atmospheric causal generation mechanism, driven by atmospheric transport and turbulence phenomena, such as eddying. Overall, we highlight the uniquely high velocity and fluid dynamic behavior of Masaya lava lake.